The Transmission of Reliable and Unreliable Information - Thomas Graeber; Shakked Noy; Christopher Roth (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Information often shapes behavior regardless of its quality: unreliable claims wield influence, while reliable ones are neglected. We propose that this occurs in part because word-of-mouth transmission tends to preserve claims while dropping information about their reliability. We conduct controlled online experiments where participants listen to economic forecasts and pass them on through voice messages. Other participants listen either to original or transmitted audio recordings and report incentivized beliefs. Across various transmitter incentive schemes, a claim's reliability is lost in transmission much more than the claim itself. Reliable and unreliable information, once filtered through transmission, impact listener beliefs similarly. Mechanism experiments show that reliability is lost not because it is perceived as less relevant or harder to transmit, but because it is less likely to come to mind during transmission. A simple associative-memory framework suggests that reliability information may be less likely to come to mind either because it is less likely to be cued by transmission requests or because attempts to retrieve it face greater interference. Evidence from our experiments, a large corpus of everyday conversations, and economic TV news supports both of these mechanisms.
Keywords: D83; 330; information transmission; word-of-mouth; reliability; memory; TV news